Increasing arterial blood pressure with norepinephrine does not improve microcirculatory blood flow: A prospective study - Dubin, Arnaldo (2009)
Introduction: Our goal was to assess the effects of titration of a norepinephrine infusion to increasing levels of mean arterial pressure (MAP) on sublingual microcirculation. Methods: Twenty septic shock patients were prospectively studied in two teaching intensive care units. The patients were mechanically ventilated and required norepinephrine to maintain a mean arterial pressure (MAP) of 65 mmHg. We measured systemic hemodynamics, oxygen transport and consumption (DO2 and VO2), lactate, albumin-corrected anion gap, and gastric intramucosal-arterial PCO2 difference (ΔPCO2). Sublingual microcirculation was evaluated by sidestream darkfield (SDF) imaging. After basal measurements at a MAP of 65 mmHg, norepinephrine was titrated to reach a MAP of 75 mmHg, and then to 85 mmHg. Data were analyzed using repeated measurements ANOVA and Dunnett test. Linear trends between the different variables and increasing levels of MAP were calculated. Results: Increasing doses of norepinephrine reached the target values of MAP. The cardiac index, pulmonary pressures, systemic vascular resistance, and left and right ventricular stroke work indexes increased as norepinephrine infusion was augmented. Heart rate, DO2 and VO2, lactate, albumin-corrected anion gap, and ΔPCO2 remained unchanged. There were no changes in sublingual capillary microvascular flow index (2.1 ± 0.7, 2.2 ± 0.7, 2.0 ± 0.8) and the percent of perfused capillaries (72 ± 26, 71 ± 27, 67 ± 32%) for MAP values of 65, 75, and 85 mmHg, respectively. There was, however, a trend to decreased capillary perfused density (18 ± 10,17 ± 10,14 ± 2 vessels/mm2, respectively, ANOVA P = 0.09, linear trend P = 0.045). In addition, the changes of perfused capillary density at increasing MAP were inversely correlated with the basal perfused capillary density (R2 = 0.95, P < 0.0001). Conclusions: Patients with septic shock showed severe sublingual microcirculatory alterations that failed to improve with the increases in MAP with norepinephrine. Nevertheless, there was a considerable interindividual variation. Our results suggest that the increase in MAP above 65 mmHg is not an adequate approach to improve microcirculatory perfusion and might be harmful in some patients.